Environmental Impact Evaluation of Floating Solar Power Plant in Cirata Reservoir, West Java - Nugroho, Anggun; Santoso, Joko (West Science Nature and Technology, 2024)
This qualitative study investigates community perceptions of the environmental impacts of floating solar power plants (FSPPs) in Cirata Reservoir, West Java. Through semi-structured interviews and participant observations, data were collected from fifteen diverse stakeholders, including local residents, community leaders, environmental activists, government officials, and energy project developers. Thematic analysis revealed key themes and subthemes related to environmental concerns, economic implications, social impacts, technical considerations, and trust and transparency issues surrounding FSPP development. Participants expressed a range of perspectives, including support for solar energy, concerns about habitat disruption and water quality degradation, and calls for inclusive decision-making processes and transparent communication. The findings underscore the importance of addressing community concerns and incorporating local perspectives into the planning and implementation of FSPP projects to ensure environmental sustainability and social acceptance.